Новая гипотеза и физические основы возникновения чëточной молнии в атмосфере Земли - Баранов, М.И. (Електротехніка і електромеханіка, 2016)
Приведены новая гипотеза и базирующиеся на ней физические основы возникновения в воздушной атмосфере Земли
чëточной молнии (ЧМ). Показано, что в основе электрофизического механизма формирования этого вида молнии
находится волновое продольное распределение свободных электронов, движущихся в плазменном канале линейной
молнии (ЛМ) на стадии протекания в нем длительной компоненты тока грозового разряда. Из-за малой плотности
тока в плазменном канале ЛМ на данной стадии разряда в нем происходит образование таких относительно длительно существующих волновых электронных пакетов, которые характеризуются сравнительно большими и поэтому визуально видимыми наблюдателями вначале ЛМ и затем ЧМ размерами своих периодически распределенных
вдоль канала молнии «горячих» («светлых») и «холодных» («темных») продольных участков. Наведено нова гіпотеза і фізичні основи виникнення в повітряній атмосфері Землі четочної блискавки (ЧБ). Показано,
що в основі електрофізичного механізму формування цього виду блискавки знаходиться хвилевий подовжній розподіл
вільних електронів, що рухаються в плазмовому каналі лінійної блискавки (ЛБ) на стадії протікання в нім тривалою
компоненти струму грозового розряду. Із-за малої щільності струму в плазмовому каналі ЛБ на даній стадії розряду в нім
відбувається утворення таких відносно тривало існуючих хвилевих електронних пакетів, які характеризуються порівняно великими і тому візуально видимими спостерігачами спочатку ЛБ і потім ЧБ розмірами своїх періодично розподілених уздовж каналу блискавки «гарячих» («світлих») і «холодних» («темних») подовжніх ділянок. Purpose. Development and scientific ground of new hypothesis
of origin of rosary lightning (RL) is in the air atmosphere of
Earth. Methodology. Electrophysics bases of technique of high
(ever-higher) impulsive voltage and large (weak) impulsive
currents, and also theoretical bases of quantum physics. Results. The substantive provisions of new hypothesis of origin
are formulated RL. Taking into account these positions bases
of close electrophysics theory of origin are developed in an air
atmosphere RL. Basic electrophysics terms, resulting in the
transition of linear lightning (LL) in RL, are indicated. Originality. First on the basis of conformities to the law of quantum
physics the new electrophysics mechanism of education is
offered RL from LL. It is set that this mechanism the wave
longitudinal distributing of drifting lone electrons is underlaid
in the plasma cylindrical channel of a long spark storm digit
in an air atmosphere, resulting in forming in him of «light»
(«hot») and «dark» («cold») longitudinal areas of periodic
electronic wavepackages (EWP). It is shown that for LL information the areas of EWP periodically up-diffused along the
channel of lightning are characterized the small and unnoticeable for observers lengths, and for RL − by large lengths and
by sight noticeable for observers from earth. Practical value.
Deepening of scientific knowledges about physics of such
global atmospheric phenomenon as lightning. Expansion of
scientific presentations of humanity about circumferential
tellurians nature and difficult natural physical processes,
flowings in it.